Binongko people's life in Coral Island - Hamid, Abd. Rahman (Wacana, Journal of the Humanities of Indonesia, 2016)
This article looks at the life of Binongko people. The word "Binongko" is well known as a Buton migrant's identity from Southeast Sulawesi in Maluku. In fact, it is a name of a rock island in Wakatobi district. Few people know about this fact. Binongko people built their world through the myth of La Patua Sakti and Putri Bidadari. Since the environment did not support farming activities, most of the people's needs were supplied by the sea through sailing. This activity was as old as their history in this island. The people also developed their skills as blacksmiths, which supported sailing tradition. This profession was an old identity of Wakatobi. This island brought about: early migrants of Buton in Maluku, skilful sailors, and ulamas, who were hard-working people. This study finds the relationships between the environment, history and culture of Binongko people in Wakatobi area.